Evaluasi Perhitungan Tarif Pelayanan Jasa pada Balai Karantina Pertanian Kelas 1 Pontianak Dengan Metode Activity Based Costing - AKHIR, MAULIDIA (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
Â This study aims to analyze the calculation of quarantine action service rates at the Balai Karantina Pertanian Kelas 1 Pontianak which are considered to be quite expensive. This research is a qualitative study using a descriptive approach that is supported by primary data as research instruments. Primary data in the form of financial information and information related to service activities obtained through interviews and observations, are processed using the Activity Based Costing method whose results are compared with the results of calculations with traditional methods.The results of this study indicate the occurrence of over cost caused by the application of cost calculations by traditional methods. From the comparison made the difference in the calculation of the service fee of Rp. 14,347,340 where the overhead costs are charged too much into the quarantine service costs.